Design and Prototyping of a Visitor Counter Guide for Single Entry and Exit. - Iragaba, Apollo (Kabale University, 2025)
Nowadays there is a need for visitor counting machines in various places for planning, organizing, and estimation purposes regarding many customers in the case of malls, shops, also in museums for saving resources. Due to time management and a large population, it is not possible to count a number of individuals manually. This project has devised an alternative system of determining the number of people in a building by employing a microcontroller, an LM7805 voltage regulating chip, double light sensors, and an LCD. The first chapter is the introduction, the problem statement, project objectives, significance and justification, and the scope. A review of the literature on which the project emerged is represented in chapter two. The third chapter gives the methodology followed in transforming from a problem to a solution while the fourth is a presentation of the findings and results of the project. These results are later discussed in the sixth chapter. References and extra points that need to be reported are shown thereafter.